2015
DOI: 10.1111/anae.12988
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fibreoptic‐guided tracheal intubation through the Ambu®Aura‐i, the intubating laryngeal mask airway and the i‐gel: a manikin study

Abstract: SummaryWe compared the Aura-i TM , intubating laryngeal mask airway and i-gel TM as conduits for fibreoptic-guided tracheal intubation in a manikin. Thirty anaesthetists each performed two tracheal intubations through each device, a total of 180 intubations. (22-35 [14-59]) s for the Aura-i, intubating laryngeal mask airway and i-gel, respectively. Tracheal intubation through the i-gel was the quickest (p < 0.01). Resistance to railroading of the tracheal tube over the fibrescope was significantly greater thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The authors have reasoned that Aura-i has a flat angle of exit, which may result in the fibrescope or tracheal tube exiting more posteriorly and heading towards the oesophagus. [ 21 ] Furthermore, all patients who required two attempts at intubation had an initial Brimacombe grade of ≤2.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have reasoned that Aura-i has a flat angle of exit, which may result in the fibrescope or tracheal tube exiting more posteriorly and heading towards the oesophagus. [ 21 ] Furthermore, all patients who required two attempts at intubation had an initial Brimacombe grade of ≤2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, de Lloyd et al [ 25 ] compared the three intubating SAD, Aura-i, FT-LMA, and i-gel as conduits for fiberoptic-guided tracheal intubation in a randomized and crossover manner in a manikin study and concluded that the Aura-i does not perform well as compared with FT-LMA or the i-gel as an adjunct for performing fiberoptic-guided tracheal intubation. They explained the lower success rate with Aura-i because of the flatter angle of exit at distal portion, which may result in the tracheal tube leaving fiberscope more posteriorly and directing towards the esophagus, as compared with FT-LMA and i-gel, which have an elevated exit course.…”
Section: Discussionmentioning
confidence: 99%
“…It is appropriate to perform endotracheal intubation through intubating LMAs utilizing fibrobrochoscope after recovery of spontaneous circulation. [27] de Lloyd et al [28] compared Aura-i and i-gel for fibreoptic-guided tracheal intubation in a manikin and showed quicker endotracheal intubation through i-gel and more failures through the Aura-i. Second, it was a manikin-based study that may not be definitively extrapolated to clinical application.…”
Section: Discussionmentioning
confidence: 99%